Especificação de testes funcionais usando Redes de Petri a objetos para softwares orientados a objetos - Vale, Liliane do Nascimento (2009)
The main purposed of this paper is to show the formalization of functional tests spec- ifying then with Object Petri Nets and Workflow-Nets in relation to software focused on objects. Initially, Workflow-Nets are used to represent the main requirements of the soft- ware. Next, Object Workflow-Nets derived from Workflow-Nets and Objects Petri Nets are used to specify formally the test models of many software functionalities. The pro- posed models allow complex data structures to be represented during the test, concerning each one of the many functions to be worked out. The execution of the model functional test, when considering a software architecture, is given by the instantiation of a test class associated with the tested functionality. To enlight this model, a concret study of it is applied to the functionality tests of a commercial software of automobile parts, developed in the ambit academic and marketed.